Feasibility Analysis and Production Increase Strategy for Marine Ornamental Fish Agribusiness - Mauli Kasmi; Andryanto Aman; Andi Ridwan Makkulawu; Syamsul Marlin Amir; Akmal Abdullah; Arif Fuddin Usman (Jurnal Penelitian Pendidikan IPA, 2023)
The marine ornamental fish business has experienced significant growth every year in Indonesia. This study aims to conduct feasible business analysis for marine ornamental fish commodities at PT. Indotama Putra Wahana. This study aims to evaluate the financial feasibility and investment in the marine ornamental fish business by achieving maximum sustainable profits. The research was conducted from March to July 2023. Data collection was carried out using primary and secondary data using interview methods and direct field observations (PT. Indotama Putra Wahana, DKI Jakarta). Data were analyzed using NPV (Net Present Value), Payback Period, Profitability Index, IRR (Internal Rate of Return), and BEP (Break Even Point). The results show that the NPV of cash flows for 10 years with a discount rate of 20% has a Profitability Index of 1.2. This indicates that the marine ornamental fish business has promising prospects. Data analysis also shows that the payback period is 3.4 years, the Net Present Value is IDR 9.972.734.254, and the IRR (Internal Rate of Return) is 21.8% which exceeds the interest rate of 11.5%. Break Even Point (BEP) of IDR 1.489.913.724 or 8.343 fish. These values indicate that this marine ornamental fish business generates positive income or profits.